El gran libro de los pequenos curiosos - Antoine, Heloise; Godon, Ingrid; Scheurer, Christianne ([Barcelona] : Juventud, 1998)
A thematic listing of words for everyday objects with accompanying illustrations of those objects and a young boy and girl engaged in activity related to each theme.
Translation of: Le grand catalogue des petits curieux.
Keywords: Spanish language -- Vocabulary